2007
DOI: 10.1117/12.715178
|View full text |Cite
|
Sign up to set email alerts
|

Innovative high-power CW Yb:YAG cryogenic laser

Abstract: In this paper we discuss a CW Yb:YAG cryogenic laser program that has resulted in the design and demonstration of a novel high power laser. Cryogenically-cooled crystalline solid-state lasers, and Yb:YAG lasers in particular, are attractive sources of scalable CW output power with very high wallplug efficiency and excellent beam-quality that is independent of the output power. This laser consists of a distributed array of seven highly-doped thin Yb:YAG-sapphire disks in a folded multiple-Z resonator. Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…A passive cryogenic cooling system ultimately has scalability limitations whereas an active cooling system allows scalability far beyond that achievable with a passive dewar. The goal of this project is to extend the performance reported at this conference last year [9] to over 500 W, and ultimately to > 1 kW. A cryogenically-cooled Yb:YAG laser with a practical, robust, and highly scalable resonator that was capable of > 1 kW CW output and near diffraction-limited beam quality in a compact package was used.…”
Section: Introductionmentioning
confidence: 99%
“…A passive cryogenic cooling system ultimately has scalability limitations whereas an active cooling system allows scalability far beyond that achievable with a passive dewar. The goal of this project is to extend the performance reported at this conference last year [9] to over 500 W, and ultimately to > 1 kW. A cryogenically-cooled Yb:YAG laser with a practical, robust, and highly scalable resonator that was capable of > 1 kW CW output and near diffraction-limited beam quality in a compact package was used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have shown that Yb:YAG is almost ideally suited for use at cryogenic temperatures [8][9][10]. Among the relevant laser hosts tested, they showed that crystalline YAG has the highest thermal conductivity, the lowest thermal expansion coefficient and the smallest dn/dT.…”
Section: Introductionmentioning
confidence: 99%
“…As the laser head is cooled the aluminum annulus contracts differentially onto the molybdenum, thereby firmly clamping it and greatly reducing the thermal resistance between the slab and the cryostat. While we considered other materials such as undoped YAG and sapphire [10] for the material in contact with the slab, we finally chose molybdenum because of the close match between the integrated coefficient of thermal expansion of Mo [16] and YAG [6] over the temperature range considered. Mo also has high thermal conductivity at 77 K, and is readily machinable, resulting in a practical design.…”
Section: Cryogenic Laser Head Designmentioning
confidence: 99%
“…The magnitudes of these effects are determined by the thermo-mechanical and thermo-optical properties of the material and they reduce significantly at cryogenic temperatures, suggesting a very promising approach for power scaling [1]. The predicted improvements in laser performance have been partially demonstrated in thin Yb:YAG-sapphire disks [2] and rods [3]. However associated with these choices are limitations due to the geometry.…”
Section: Introductionmentioning
confidence: 99%